2020
DOI: 10.3390/met10121585
|View full text |Cite
|
Sign up to set email alerts
|

Improving Hydrogen Embrittlement Resistance of Hot-Stamped 1500 MPa Steel Parts That Have Undergone a Q&P Treatment by the Design of Retained Austenite and Martensite Matrix

Abstract: Hydrogen embrittlement is one of the largest obstacles against the commercialisation of ultra-high strength quenching and partitioning (Q&P) steels with ultimate tensile strength over 1500 MPa, including the hot stamped steel parts that have undergone a Q&P treatment. In this work, the influence of partitioning temperature on hydrogen embrittlement of ultra-high strength Q&P steels is studied by pre-charged tensile tests with both dog-bone and notched samples. It is found that hydrogen embrittlemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Wang and Huang [10] showed that the hydrogen embrittlement resistance of an ultrahigh-strength Fe-0.3C-1-57Si-2.94Mn Q&P steel can be improved by applying a higher partitioning temperature (450 • C). Partitioning temperature did not affect the hydrogen trapping properties of the Q&P-treated steel.…”
Section: Contributionsmentioning
confidence: 99%
“…Wang and Huang [10] showed that the hydrogen embrittlement resistance of an ultrahigh-strength Fe-0.3C-1-57Si-2.94Mn Q&P steel can be improved by applying a higher partitioning temperature (450 • C). Partitioning temperature did not affect the hydrogen trapping properties of the Q&P-treated steel.…”
Section: Contributionsmentioning
confidence: 99%
“…in fact, using hydrogen as fuel in gas turbines can deteriorate the mechanical properties of ni-based superalloys [11][12][13][14]. Because hydrogen permeates to the surface of a specimen by electrochemical hydrogen charging [15,16], the geometry of a specimen may affect the sensitivity to hydrogen embrittlement. in ni-based alloys, various studies on test conditions such as test temperature, strain rate, and heat treat conditions have been conducted [13,14], but studies on hydrogen embrittlement according to the specimen geometry have not been conducted.…”
Section: Introductionmentioning
confidence: 99%